2019
DOI: 10.1002/anie.201813288
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Regulation of DNA i‐Motifs for Nanobiotechnology and Therapeutics

Abstract: DNA sequences rich in cytosine have the propensity, under acidic pH, to fold into four‐stranded intercalated DNA structures called i‐motifs. Recent studies have provided significant breakthroughs that demonstrate how chemists can manipulate these structures for nanobiotechnology and therapeutics. The first section of this Minireview discusses the development of advanced functional nanostructures by synthetic conjugation of i‐motifs with organic scaffolds and metal nanoparticles and their role in therapeutics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 154 publications
0
41
0
Order By: Relevance
“…Both the nanofibrous structure and the rheological results confirmed that the formed solid DNAm aterials were hydrogels. [12] Remarkably,t he G' value and G'' value reached 9 10 4 Pa and 2 10 4 Pa, respectively ( Figure 2G), which were much higher than that of almost all the previously reported pure DNAh ydrogels. [12d, 19] Fort he underlying mechanism, we speculated that the unique condensing fibrous structure of the hydrogel might be responsible for the high mechanical strength ( Figure S5).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Both the nanofibrous structure and the rheological results confirmed that the formed solid DNAm aterials were hydrogels. [12] Remarkably,t he G' value and G'' value reached 9 10 4 Pa and 2 10 4 Pa, respectively ( Figure 2G), which were much higher than that of almost all the previously reported pure DNAh ydrogels. [12d, 19] Fort he underlying mechanism, we speculated that the unique condensing fibrous structure of the hydrogel might be responsible for the high mechanical strength ( Figure S5).…”
Section: Resultsmentioning
confidence: 65%
“…[11] In particular,the imotif DNAused in this study is aDNA quadruplex structure stabilized by hemi-protonated cytosine-cytosine + (C:C + )base pairs in acidic medium, which has been widely applied in the preparation of dynamic self-assembled structures. [12] Herein, we designed and synthesized ad ouble-stranded DNA (dsDNA) that was capable of forming i-motif DNAa s building unit, and by using the dsDNA, we constructed ad ynamic DNAs elf-assembly system which achieved lysosomal acidic stimuli specifically mediated topological transformation from nanoparticles to ap hase separated and organelle-like hydrogel architecture in living cells.The effects of the organelle-like hydrogel architecture on behaviors of both cancer and normal cells were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that i-motif can exist under neutral or physiological pH under molecular crowding conditions or in the presence of some cations [7,8]. I-motif structure might play important regulatory roles in biological processes, such as DNA replication, gene transcription, and maintenance of genomic stability [9]. Some i-motif I-motif structure might play important regulatory roles in biological processes, such as DNA replication, gene transcription, and maintenance of genomic stability [9].…”
Section: Introductionmentioning
confidence: 99%
“…I-motif structure might play important regulatory roles in biological processes, such as DNA replication, gene transcription, and maintenance of genomic stability [9]. Some i-motif I-motif structure might play important regulatory roles in biological processes, such as DNA replication, gene transcription, and maintenance of genomic stability [9]. Some imotif structures in oncogene promoters have been indicated for regulating gene transcriptions, including PDGFR-β, c-myc, BCL2, and KRAS [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] The pH responsive structure and reversible conformational switching properties of i-motifs have been potentially used in DNA nanotechnology. [17][18][19][20] However, i-motifs have been less investigated for designing ligands for therapeutics [21][22][23] as compared to complementary G-quadruplexes (G 4 s) that have been well studied in the past decade. [24][25][26] The reported i-motif ligands such as the cationic porphyrin TmPyP4, 27 phenanthroline derivatives, 28 neomycin-perylene conjugates, 29 crystal violet, 30 Thioavin T 31,32 and berberine 33 do not show signicant selectivity for i-motif structures over duplex and quadruplex structures.…”
Section: Introductionmentioning
confidence: 99%